A Narrow Wall System to Capture Temperature Stress–Strain Behaviorin Paste Backfill - Wee, Kiet Ting; Alsidqi, Hasan; Fauzan, Sahdi; Siti Noor Linda, Taib; Norsuzailina, Mohamed Sutan; Badhrulhisham, Abdul Aziz; Andy, Fourie (ASTM, 2019)
Placing mine tailings back into underground mined-out stopes is becoming increasingly usedinternationally because it improves ore recovery, reduces dilution of valuable ore, andincreases environmental benefits due to the reduced size of the storage facilities of surfacetailings. In recent years, a number of stopes backfilled with cemented paste backfill have beeninstrumented with load cells and piezometers to improve our understanding of in situ behavior.Many of these studies have reported results that show increases in measured total stresseswhen there is no increase in applied load, i.e., even when the backfilling process has been longcompleted. One explanation is that these stress increases result from expansive volumechanges of the backfill as it hydrates and generates heat. This article proposes and describesa novel laboratory apparatus called a narrow wall system to investigate this hypothesis, focus-ing on modeling narrow stopes as these are relatively common in backfill applications. Resultsfrom the experiments agree qualitatively with the reported field observations, showing clearincreases in measured pressure during periods of temperature increase. The article concludesthat the proposed narrow wall system works effectively and has been able to capture thetemperature stress–strain behavior of paste backfill. Thus, the temperature effect hypothesishas now been supported by evidence. Using the system, further studies related to geometricalor scale effects are suggested. The results are important for academics and engineers toimprove backfill design in mining operations